Ideais perfeitos de codimensão 2 em três variáveis - Feitosa, Cássio Anderson (2019)
In this work, we will study properties of ideals of codimension 2 generated by maximals minors of a n×(n−1) matrix ϕ with linear entries in the polynomial ring k[x,y,z], with k a ﬁeld. Speciﬁcally, on the light of the chaos invariant of the matrix ϕ, we will explore properties of the Rees algebra and special ﬁber of ideals of this class, especially in the case where the chaos invariant is equal to 1.